2018
DOI: 10.1038/s41467-018-03247-3
|View full text |Cite|
|
Sign up to set email alerts
|

Comprehensive integrative analyses identify GLT8D1 and CSNK2B as schizophrenia risk genes

Abstract: Recent genome-wide association studies (GWAS) have identified multiple risk loci that show strong associations with schizophrenia. However, pinpointing the potential causal genes at the reported loci remains a major challenge. Here we identify candidate causal genes for schizophrenia using an integrative genomic approach. Sherlock integrative analysis shows that ALMS1, GLT8D1, and CSNK2B are schizophrenia risk genes, which are validated using independent brain expression quantitative trait loci (eQTL) data and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
76
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 80 publications
(80 citation statements)
references
References 86 publications
(198 reference statements)
3
76
1
Order By: Relevance
“…Considering the fact that most of the variants identified by GWAS are located in non‐coding regions, it is reasonable to assume that these variants affect phenotypes through regulating gene expression. Previous studies (Luo et al, ; Wu et al, ; Yang et al, ; Zhong et al, ) have successfully prioritized plausible causal genes by using integrative approach of expression quantitative trait loci (eQTL) and disease association data. Nevertheless, to date, there is no relevant systematic study, incorporating data from different omics layers to identify periodontitis‐associated genes.…”
Section: Introductionmentioning
confidence: 99%
“…Considering the fact that most of the variants identified by GWAS are located in non‐coding regions, it is reasonable to assume that these variants affect phenotypes through regulating gene expression. Previous studies (Luo et al, ; Wu et al, ; Yang et al, ; Zhong et al, ) have successfully prioritized plausible causal genes by using integrative approach of expression quantitative trait loci (eQTL) and disease association data. Nevertheless, to date, there is no relevant systematic study, incorporating data from different omics layers to identify periodontitis‐associated genes.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, only based on the findings of GWAS analysis is impossible to infer whether the detected disease-associated SNPs contain regulatory functions. Thus, Sherlock integrative analysis is a good and effective method for combining the information of GWAS with eQTL data and has been applied to identify many novel risk genes of many complex diseases [15,[19][20][21][22], which cannot be detected by GWAS alone.…”
Section: Discussionmentioning
confidence: 99%
“…He et al [15] introduced a Bayesian statistical approach of Sherlock to systematically reveal the cis-and trans-regulatory effects of risk genes on complex diseases based on GWAS summary data and eQTL data. By using this bioinformatics tool, numerous studies have identified many novel risk genes, which cannot be found with the use of the GWAS approach alone, for different complex traits, such as schizophrenia [19], gout disease [20], and major depressive disorders [21,22].…”
Section: Introductionmentioning
confidence: 99%
“…Evidence suggest that noncoding variants identified by GWASs may be involved in transcriptional mechanisms (Maurano & Stamatoyannopoulos, ; Lucas D. Ward & Kellis, ) and thus co‐localizing the noncoding variants with expression quantitative trait loci (eQTL) could provide insights into gene expression regulation (Westra et al, ) and biological basis for disease associations (Cookson, Liang, Abecasis, Moffatt, & Lathrop, ; Degner et al, ). Such integrative studies have been performed successfully in multiple psychiatric disorders (Cross‐Disorder Group of the Psychiatric Genomics Consortium, ), including schizophrenia (Luo et al, ; Yang, Li, et al, ), autism spectrum disorder (Wang et al, ), attention deficit‐hyperactivity disorder (Yang, Chang, et al, ), bipolar disorder (Li et al, ), and major depressive disorder (Huo et al, ). Integrating GWAS signals of DD with eQTLs derived from human brain tissues will be useful to identify any functional variants.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, neurodevelopmental disorders (e.g., schizophrenia, autism, epilepsy and intellectual disability) could share a genetic base (Brainstorm et al, ) and some core clinical features and molecular regulatory networks (Parikshak, Gandal, & Geschwind, ), particularly in human brain tissues (Johnson et al, ). It is therefore plausible to borrow functional genomic information from other neurodevelopmental disorders such as schizophrenia (Yang, Li, et al, ) to inform research in DD where sample resources (e.g., human brain tissues) and cell models are generally lacking. For example, differential gene expression data derived from a well‐powered study of schizophrenia might be valuable to study functional roles of the DD susceptible genes.…”
Section: Introductionmentioning
confidence: 99%